1995
DOI: 10.1007/bf01076076
|View full text |Cite
|
Sign up to set email alerts
|

Myristoylation of endothelial cell nitric oxide synthase is important for extracellular release of nitric oxide

Abstract: Endothelial cell nitric oxide synthase (NOS) is known to have a N-myristoylation consensus sequence. Such a consensus sequence is not evident in the macrophage, smooth muscle and neuronal NOS. A functional role for this N-terminal myristoylation is not clear yet. In the present study, we examined the effect of N-terminal myristoylation on the NOS activity determined by the conversion of L-[3H]arginine to L-[3H]citrulline and extracellular NO release determined by nitrite production in the conditioned medium fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 25 publications
2
28
0
2
Order By: Relevance
“…However, there is ample evidence for a functional role of Golgi complex-localized eNOS. As originally described in transfected cells (33,37), eNOS is found in the peripheral aspects of the Golgi complex, and this targeting is required for optimal NO release from cells. More recently, using immunofluorescence microscopy to label eNOS phosphorylated at Ser 1179 and NO imaging with 4,5-diaminofluorescein diacetate, we found that, in response to the angiogenic vascular endothelial growth factor, Golgi complex-localized eNOS is phosphorylated at Ser 1179 , and we identified "bursts" of NO emanating from the perinuclear region of endothelial cells (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is ample evidence for a functional role of Golgi complex-localized eNOS. As originally described in transfected cells (33,37), eNOS is found in the peripheral aspects of the Golgi complex, and this targeting is required for optimal NO release from cells. More recently, using immunofluorescence microscopy to label eNOS phosphorylated at Ser 1179 and NO imaging with 4,5-diaminofluorescein diacetate, we found that, in response to the angiogenic vascular endothelial growth factor, Golgi complex-localized eNOS is phosphorylated at Ser 1179 , and we identified "bursts" of NO emanating from the perinuclear region of endothelial cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that WT and G2A eNOS have similar catalytic abilities and cofactor requirements (38,39) despite the inability of mislocalized G2A eNOS to produce NO after stimulation of cells with calcium-mobilizing agonists (33,37). Therefore, we measured the catalytic competency of the newly generated eNOS fusion proteins in vitro using the conversion of L-[ 3 H]arginine to L-[ 3 H]citrulline as an index of NOS activity in detergent-solubilized COS cell extracts.…”
Section: Generation and Characterization Of Enos Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Myristoylation and dual palmitoylation at its extreme N terminus target eNOS to the cytoplasmic face of the Golgi complex and to the plasma membrane (7), where eNOS is thought to be fully capable of activation (8,9). Misrouting of acylation-deficient eNOS impairs NO production (10,11), indicating that correct subcellular targeting is critical for stimulus-dependent activation of the enzyme (8). Posttranslational modifications are efficiently complemented by multiple proteinprotein interactions that help regulate eNOS activity with respect to time and space.…”
mentioning
confidence: 99%
“…Subcellular localization of eNOS: eNOS is largely membrane-associated as a result of Nterminal myristoylation and palmitoylation modifications (30,152,157 translocates remain unclear, but many include the nuclear membrane, the endoplasmic reticulum, or trans-golgi system (83).…”
Section: Endothelial Nitric Oxide Synthase (Enos)mentioning
confidence: 99%